A decade of development studies from Iberoamerican perspective - Gutiérrez-Nieto, Begoña; Larrú-Ramos, José María; Marcuello-Servós, Chaime (Iberoamerican Journal of Development Studies, 2022)
The Iberoamerican Journal of Development Studies celebrates ten years. It is time to recognize who supports it, the characteristics that have led it to advance in Development research, in addition to achieving international recognition, and to give thanks to so many people who have supported it and to those who today contribute their great value as a team.